A kinetic ruler controls mRNA poly(A) tail length - Gabs, Emilie; Aalto-Setälä, Emil; Välisaari, Aada; Malinen, Anssi M.; Jensen, Torben Heick; McLaughlin, Stephen H.; Passmore, Lori A.; Turtola, Matti (Cold Spring Harbor Laboratory, 2026)
Poly(A) tails of newly synthesized mRNAs have uniform lengths, arising through cooperation between the cleavage and polyadenylation complex (CPAC) and poly(A) binding proteins (PABPs). In the budding yeast Saccharomyces cerevisiae, the responsible PABP is the evolutionarily conserved CCCH zinc finger protein Nab2 that facilitates the biogenesis of ∼60 adenosine mRNA poly(A) tails. Here, we address the molecular basis for such length control. Reconstituting polyadenylation reactions during the formation of Nab2:poly(A) RNA ribonucleoprotein particles in vitro, we found that Nab2 dimerization directs polyadenylation termination. The Nab2 dimer is stable only on poly(A) tails that are >25 adenosines, explaining how Nab2 avoids prematurely terminating poly(A) synthesis. However, the mature tail length is not determined by the footprint of Nab2 on the RNA but rather by the kinetic competition between CPAC-mediated tail elongation and Nab2 RNA binding. Variations in Nab2 RNA binding rate can shift poly(A) tail lengths, but in cells such variations are buffered by autoregulation of Nab2 protein concentration. As a result, poly(A) tail length control operates through a “kinetic ruler” mechanism, whereby the concentration of Nab2 quantifies RNA length.